Assistance in Independent Fish Feed Production at POKDAKAN Mina Mandiri, Panembangan Village Banyumas: Pendampingan Pembuatan Pakan ikan Mandiri Pada POKDAKAN Mina Mandiri Desa Panembangan Banyumas - Purnama Sukardi; Mustika Palupi; Rudy Wijaya; Fitriadi, Ren; Kothoh Syuraikhanah; Indra Hariman; Ufianah, Ufianah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of this activity is to improve the competence of fish feed manufacturing and can increase fish sales production. The approach method carried out in this activity is a participatory Participatory Rural Appraisal (PRA) approach starting with a survey and problem identification, socialization and counseling training on making fish meal, training and direct technical guidance on making feed formulations, and assistance in making fish feed. The result of this dedication is that partners know the technology of making feed using available and abundant ingredients so as to reduce production expenditure in fish farming. Counseling and training activities in community service received good enthusiasm from members and partners of direct participants in making fish feed. The result of service activities is that partners gain knowledge and skills in making independent fish feed from waste and local raw materials. Making independent feed is able to increase production profits by reducing production costs incurred. The potential for developing activities can encourage productivity and provision of skills that can be disseminated to the wider community.